Den umulige kommunikasjonen i Lene Asks "Det du ikke sier, er sant" - Christensen, Sofija (Nordlit, 2022)
The protagonist of Lene Ask’s novel Det du ikke sier, er sant (What you don’t say is true (2017)) is Kamran, a young teenager who resorts to lies when he is unsure of what to say. The main theme of the novel concerns the development of Kamran’s language use and his growth into an autonomous subject in the communication with others. The book’s protagonist, theme and treatment of the theme may appeal to young readers. The novel portrays language, truth, and lying in a way that invites the reader to critically examine their own perceptions of these, especially through the novel’s explicit intertextuality with Henrik Ibsen’s Peer Gynt. The novel may to a certain degree be categorized as a so-called complex or challenging text. The article argues for the novel’s potential in exploratory literature teaching. The author explores the possible meanings of the title to indicate three different ways one might approach the literary presentation of Kamran’s mastering of communication and language.
Keywords: children's literature; communication; challenging YA novels; exploratory literature teaching; young adult fiction